Analisis Strategi Pemasaran Dan Penjualan E-Commerce Pada Lazada.Co.Id - Dwi Rani Rahayu; Natasya Salsabila Nainggolan; M. Raihan; Nurbaiti Nurbaiti (Universitas 45 Surabaya, 2024)
The purpose of this research is to determine the marketing and sales strategies for e-commerce at lazada.co.id. This research uses a qualitative method with an inductive approach. Based on the analysis of Lazada.co.id's marketing and sales strategies, we found that the Lazada website is a fairly large online marketplace in Indonesia that allows Indonesian individuals and business owners to manage their stores online easily and for free. Lazada offers everything from secure payment options to marketing analytics designed to help Lazada sellers sell more products. The marketing strategy carried out by Lazada.co.id begins with promotions on the Lazada website. Lazada.co.id has an effective website where visitors can easily access product and promotional information in the form of text and images. Apart from that, Lazada markets via social media and television.